Дискусійні питання передопераційної підготовки, інтра- та поопераційного ведення хворих із тиреотоксикозом - Щупачинська, Л. О.; Мельник, А. В.; Болгов, М. Ю. (Clinical Endocrinology and Endocrine Surgery, 2010)
Based on their own experience autors underline that in severe course of thyrotoxicosis the state of drug-induced euthyroidism does not always correspond to clinical compensation especially in heart and vascular system. For various body systems that were under toxic effect of abundant thyroid hormones time is needed for restoration and adaptation to normal level of thyroid hormones. Demonstrative clinical case is shown.